Поперечные колебания жидкости в длинном цилиндрическом контейнере с мембраной или упругой пластинкой на свободной поверхности - Троценко, В.А.; Богун, Р.И. (Нелінійні коливання, 2009)
Запропоновано наближенi розв’язки двовимiрних задач гiдропружностi, що описують вiльнi коливання iдеальної рiдини в горизонтально розмiщеному довгому цилiндричному контейнерi з
довiльним симетричним поперечним перерiзом, вiльна поверхня якої покрита плоскою мембраною або пружною пластинкою. На конкретних прикладах наведено аналiз отриманих розв’язкiв
та результати розрахунку частот i форм коливань механiчної системи, що розглядається. We propose a construction of approximate solutions to two-dimensional hydroelastic problems that describe free oscillations of an ideal fluid in a horizontally placed long cylindrical container with an arbitrary
symmetric cross-section. The free surface of the fluid is covered with a plane membrane or an elastic plate.
Using concrete examples, we analyze the obtained solutions and the results of the calculations of frequencies, and the form of oscillations of the mechanical system under consideration.